Investigating the Impact of Different Oil Production Processes on the Quality and Flavor Characteristics of Hainan Camellia Oil Based on E-nose, GC-MS, and GC-IMS Analyses - Tao LAN; Lipin CHEN; Tao WANG; Meizhen XIE; Weimin ZHANG; Yonghuan YUN; Liangxiao ZHANG (Shipin gongye ke-ji)
To clarify the impact of oil extraction processes on the overall quality and flavor of Hainan camellia oil, the quality and flavor characteristics of oils extracted by pressing (NT-P, HT-P), subcritical butane extraction (NT-SBE, HT-SBE), and supercritical CO2 extraction (NT-SCE, HT-SCE) under ambient and high temperatures were compared in this study, with the aim of exploring the optimal processing technology. The impact of six different processes on the oil yield, oil quality indicators, and volatile substances of Hainan camellia oil was subjected to in-depth analysis in this study. Volatile compounds were identified using a comprehensive range of techniques, including electronic nose, headspace-solid phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS), and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). Moreover, the differences between oils treated by different processes were comprehensively and thoroughly assessed using multivariate statistical analysis. The results demonstrated that the oil yield and quality indicators of camellia oil were significantly affected by different processes (P<0.05), with HT-SCE having the highest oil yield (32.22%). The oil samples from NT-SBE, NT-SBE, HT-SBE and HT-P, HT-P were found to have the lowest acid value (0.66 mg/g), iodine value (77 g/100 g), peroxide value (0.02 g/100 g), and water content (0.03 g/100 g), respectively. The content of unsaturated fatty acids in the oil sample from NT-SCE was determined to be the highest (86.606%). A total of 160 volatile substances were detected in the six oil samples, among which aldehydes, ketones, alcohols, and some terpenoid compounds were found to make a greater contribution to the formation of the flavor of Hainan camellia oil. Camellia oil subjected to high-temperature treatment was found to contain a higher amount of aldehydes, ketones, and esters. Among the six oil samples, HT-PO was found to have the highest content of volatile substances, followed by HT-SCEO. Finally, 29 volatile compounds that made a greater contribution to the flavor of Hainan camellia oil were screened out using orthogonal partial least squares discriminant analysis (OPLS-DA), and it was found that there was a significant difference in the characteristic flavors of the oil samples from different processes (P<0.05). By comparing the quality indicators and flavor characteristics, it was found that the supercritical CO2 process is more suitable for the processing of Hainan camellia oil, providing a theoretical reference for the selection of processing technology for Hainan camellia oil.